Varied Impacts of Globalization on Religion in a Contemporary Society - Iqbal, Asep Muhamad (Program Studi Studi Agama-Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2016)
This article discusses the current situation of religion caused by the forces of globalization by analyzing the developing phenomenon related to religion in contemporary society. It argues that globalization has a mixed impact on religion in ways that lead to the opposing view of secularist scholars that religion will be diminished. Apparently, religion has experienced a revival in many parts of the world, mainly in the form of religious fundamentalism. Problems and challenges posed by globalization, such as the environmental crisis and secular society have provided the opportunity and the power to religion to revitalize itself and to transform themselves into a religion with a new form that has a role and a new identity. Furthermore, globalization may lead to the decline of organized religion in modern society and certain intellectual subculture, but it does not cause the death of religion in private life. This is in line with the emergence of the phenomenon of “believing without belonging”. In short, globalization has helped to transform the religion itself and changed its strategy to address the problems and challenges of globalization to create “world de-secularization”. [Artikel ini membahas keadaan mutakhir agama yang diakibatkan oleh kekuatan-kekuatan globalisasi dengan melakukan analisa atas fenomena yang sedang berkembang terkait agama dalam masyarakat kontemporer. Ia berargumen bahwa globalisasi memiliki dampak yang beragam terhadap agama dengan cara-cara yang justru mengarah kepada kebalikan dari ramalan musnahnya agama sebagaimana dipromosikan oleh para pendukung teori sekularisme. Tampaknya, agama mengalami kebangkitan kembali di berbagai belahan dunia, utamanya dalam bentuk gerakan fundamentalisme agama. Masalah dan tantangan yang diakibatkan oleh globalisasi, seperti krisis lingkungan dan masyarakat sekuler, justru telah memberikan kesempatan dan kekuatan kepada agama untuk merevitalisasi dirinya dan melakukan transformasi diri menjadi agama dengan bentuk baru yang memiliki peranan dan identitas baru. Lebih jauh, globalisasi telah menyebabkan kemunduran agama formal pada masyarakat modern dan subkultur intelektual tertentu, meski tidak sampai menyebabkan kematian agama dalam kehidupan pribadi. Hal ini seiring munculnya fenomena “believing without belonging”. Singkat kata, globalisasi telah membantu agama mentransformasi dirinya dan mengubah strateginya dalam mengatasi berbagai masalah dan tantangan globalisasi sehingga menciptakan “desekularisasi dunia”